ChemInform Abstract: An Investigation of the Scope of the 1, 7‐Electrocyclization of α, β:γ, δ‐Conjugated Azomethine Ylides. Issue 45 (23rd October 2014) - Zhang, Weimin; Ning, Fuqiang; Varadi, Linda; Hibbs, David E.; Platts, James A.; Nyerges, Miklos; Anderson, Rosaleen J.; Groundwater, Paul W.
Abstract The periselectivity of cyclization of in situ formed azomethine ylides from aldehydes and sarcosine is investigated.